Genetic susceptibility to hepatocellular carcinoma in chromosome 22q13.31, findings of a genome‐wide association study. Issue 12 (27th November 2021) - Wang, Zhanwei; Budhu, Anuradha S; Shen, Yi; Wong, Linda Lou; Hernandez, Brenda Y; Tiirikainen, Maarit; Ma, Xiaomei; Irwin, Melinda L; Lu, Lingeng; Zhao, Hongyu; Lim, Joseph K; Taddei, Tamar; et al.
Abstract: Background and Aim: Chronic hepatitis C virus (HCV) infection, long‐term alcohol use, cigarette smoking, and obesity are the major risk factors for hepatocellular carcinoma (HCC) in the United States, but the disease risk varies substantially among individuals with these factors, suggesting host susceptibility to and gene–environment interactions in HCC. To address genetic susceptibility to HCC, we conducted a genome‐wide association study (GWAS). Methods: Two case‐control studies on HCC were conducted in the United States. DNA samples were genotyped using the Illumian microarray chip with over 710 000 single nucleotide polymorphisms (SNPs). We compared these SNPs between 705 HCC cases and 1455 population controls for their associations with HCC and verified our findings in additional studies. Results: In this GWAS, we found that two SNPs were associated with HCC at P < 5E‐8 and six SNPs at P < 5E‐6 after adjusting for age, sex, and the top three principal components (PCs). Five of the SNPs in chromosome 22q13.31, three in PNPLA3 (rs2281135, rs2896019, and rs4823173) and two in SAMM50 (rs3761472, rs3827385), were replicated in a small US case‐control study and a cohort study in Singapore. The associations remained significant after adjusting for body mass index and HCV infection. Meta‐analysis of multiple datasets indicated that these SNPs were significantly associated with HCC. Conclusions: SNPs in PNPLA3 and SAMM50 are known risk loci for nonalcoholic fatty liver disease (NAFLD) and are suspected to be associated with HCC. Our GWAS demonstrated the associations of these SNPs with HCC in a US population. Biological mechanisms underlying the relationship remain to be elucidated. Abstract : Genome‐wide association study (GWAS) showed that five SNPs in 22q13.31, three in PNPLA3 (rs2281135, rs2896019, and 4823173) and two in SAMM50 (rs3761472 and rs3827385), were associated with HCC in the United States.